Selective adsorption of biodegradable polymaleic acid for regulating the wettability difference at the fine coal–kaolinite interface - Wei Xiao; Yuping Fan; Xianshu Dong; Xiaomin Ma; Yuanpeng Fu; Yanze Mu; Maoqing Yang; Pengcheng Wen; Kangpei Jin; Dehao Li (Minerals Engineering, 2026)

A quasi-eutectic electrolyte strategy regulating chemical bond strength endows promoted ion-decoupled kinetics for high-performance aluminum-ion batteries - Wenpeng Cao; Yongde Long; Pengcheng Liu; Mingming Xie; Jinhua Luo; Kai Du; Chengjie Wang; Jingzhen Li; Jing Geng; Hanguang Fu; Yuxiang Hu (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Study on the mechanism of selective flotation separation of fine coal and kaolinite enhanced by environmentally friendly small-molecule carboxylic acids - Wei Xiao; Yuping Fan; Xiaomin Ma; Jian Niu; Maoqing Yang; Xianshu Dong; Yuanpeng Fu; Zeyu Feng; Pengcheng Wen; Yanze Mu (Minerals Engineering, 2026)

Nanoplastic interference at the air-water interface modulate the fate and toxic persistence of BHT and BHTQ: A multi-scale computational study - Xueyu Wang; Yuezu Fu; Pengcheng Zou; Xusheng Chen; Xiaoxuan Wei; Guangcai Ma; Haiying Yu (Journal of Hazardous Materials, 2026)

Canonical Wnt pathway mediates catalpol-induced epithelial differentiation of porcine metanephric mesenchymal cells - Pengcheng Ji; Yuansheng Xie; Guangrui Geng; Wenkai Guo; Jingru Bi; Bing Han; Xu Wang; Bo Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Microwave-induced phase transformation and ultrasound-driven interface reaction for Cu/Te separation - Renkun Luo; Zhonghua Li; Zhuoyu Yin; Shixing Wang; Hongliang Liu; Jiangcheng Wang; Pengcheng Zhang; Yonggang Zuo; Gengwei Zhang; Guo Lin; Libo Zhang; Likang Fu (Journal of Environmental Chemical Engineering, 2026)

Drought as a risk amplifier: The intensifying regime of compound dry-hot events in China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Jianchun Qiu; Xiaolei Fu (Atmospheric Research, 2026)

Activation of permanganate(VII) with percarbonate for enhanced oxidation of ciprofloxacin: Sustained generation of manganese intermediates - Xiang Li; Lei Fu; Hui Wu; Aiju You; Pengcheng Yao; Yufei Shi (Desalination, 2026)

A poroelastic half-space model for dynamic pile–soil interaction problem - Pengcheng Fu; Juntao Wu; Weikai Zhao; Kuihua Wang; Lvjun Tang; Xiaonan Gong (Soil Dynamics and Earthquake Engineering, 2026)

Quantitative assessment of the reservoir-induced impact on multivariate flood risk via the nonstationary Vine Copula model - Pengcheng Xu; Zhilang Zhang; Dong Wang; Vijay P. Singh; Gengxi Zhang; Xiaolei Fu; Huanyu Yang (Journal of Hydrology, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Fe-driven ROS mitigation in Leptolyngbya JSC-1: optimizing growth using response surface method - Sikandar Khan; Maryam Akhoundian; Pengcheng Fu (Extremophiles, 2026)

Smoldering Combustion-Based calorimeter integrated with Dual-GRU network for online coal Quality analysis - Xuegang Zhang; Haiyuan Fu; Zhiming Lin; Qiwen Jin; Pengcheng Jiang; Xuecheng Wu (Fuel, 2026)

Is expectation disconfirmation related to stakeholder satisfaction and willingness to engage in national parks? A case study of Shennongjia National Park in China - Yangyang Zhang; Zhen Fu; Yang Xiang; Chucai Peng; Mingjun Teng; Lixiong Zeng; Wanji Yang; Lei Pan; Pengcheng Wang (Forest Policy and Economics, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

Synergistic interplay of sonoelectrochemistry and acidity-regulated mechanisms for the selective extraction of critical metals in copper-cadmium sludge - Hongliang Liu; Likang Fu; Pengcheng Zhang; Shixing Wang; Libo Zhang (Sustainable Chemistry and Pharmacy, 2026)

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Microdroplet air-water interfaces as nanoreactors: Reshaping the atmospheric fate and multiphase risks of phthalates via NO3-initiated interfacial oxidation - Pengcheng Zou; Xueyu Wang; Sisi Cheng; Xusheng Chen; Yuezu Fu; Haiying Yu (Environmental Pollution, 2026)

Construction of small polarons in Ni2P for rapid catalytic conversion of polysulfides in lithium-sulfur batteries - Shujun Liu; Pengcheng Yao; Jun Jiang; Tong Guo; Zhijie Qi; Yunfan Zhang; Ning Zhang; Yefang Teng; Tao Chen; Xin Wang; Junwu Zhu; Yongsheng Fu (Chemical Engineering Journal, 2026)

Machine learning-based prediction of PAHs thermal desorption efficiency: Model optimization, boundary correction, and mechanistic insights - Pengcheng Fu; Meng Qi; Chunshuang Liu; Cheng Zhang; Yuhao Zhao; Zhibao Liu; Hao Wang; Dongfeng Zhao (Journal of Environmental Management, 2025)

Analytical solution for employing low-strain pile integrity test on mechanically connected spliced piles - Pengcheng Fu; Shurui Zhang; Zhongjin Wang; Juntao Wu; Kuihua Wang; Zhiqing Zhang; Lvjun Tang (Ocean Engineering, 2025)

A comprehensive review of recent progress on the drought-flood abrupt alternation - Gengxi Zhang; Huimin Wang; Thian Yew Gan; Shuyu Zhang; Jin Zhao; Xiaoling Su; Xiaolei Fu; Lijie Shi; Pengcheng Xu; Miao Lu; Chong Wang (Journal of Hydrology, 2025)

Transcriptomics revealed the regulatory mechanism of phenylalanine butyramide on the growth and biofilm formation of Lactobacillus paracasei - Xinyu Fan; Yize Li; Yin Fu; Pengcheng Chen; Dan Wu; Pu Zheng (Food Bioscience, 2025)

Simulation of Sand-Filled Nodular Pile (SFNP) installation process using DEM - Enze Yi; Juntao Wu; M.Hesham El Naggar; Kuihua Wang; Pengcheng Fu (Computers and Geotechnics, 2025)

Non-synergistic effect of marginal distribution and dependence structure of extremes triggering the future risk of compound dry-hot events in Yellow River, China - Pengcheng Xu; Tong Zhu; Dong Wang; Yuankun Wang; Vijay P. Singh; Miao Lu; Xiaolei Fu (Stochastic Environmental Research and Risk Assessment, 2025)

From Rock to Fiber: The Mechanical Properties of Continuous Rock Fibers - Yixuan Ma; Zeshi Guo; Jimin Fu; Xiongyu Xi; Pengcheng Ma; Xungai Wang (Natural Resources Research, 2025)
The mechanical properties of continuous rock fiber (CRF), particularly its elastic modulus and tensile strength, are essential requirements for the ever-increasing applications of this material. Studies on CRF have primarily focused on its application in fiber-reinforced composites, with much less emphasis on the analysis of the fiber structure–property relationship. This review summarizes and discusses the current experimental approaches, theories, models, and parameters in different production stages (geochemistry, rock screening, melting, cooling, and fiber drawing) that would affect the elastic modulus and tensile strength of CRF. For the current research results, the general debate is the trade-off between the network structure and defects in the tensile strength of CRF. The study of elastic modulus functions as the fundamental of tensile strength, as the former can be explored regardless of certain defects, only considering the microstructure of the network, local atom coordination and bonding, whereas the latter can be studied beyond characterizing the defects. The limitations of current methods include theories for crystals and stable substances, which may not be applicable to metastable monofilaments or complex CRF glasses. Experimentally, in situ testing is difficult for fibers in certain procedures that cause permanent damage. Machine learning (ML) and molecular dynamics (MD) can compensate for the lack of experimental data, reduce the effects of operational procedures, provide structure-based information, and reflect the combined effects of multiple input features. An ongoing approach should be based on a solid understanding of conventional models and improvements in standardized experimental and MD datasets incorporated with ML methods.

Dynamic response of saturated layered soil around defective piles and its application in engineering testing - Pengcheng Fu; Juntao Wu; Junjie Jia; Enze Yi; Kuihua Wang; Zhiqing Zhang (Soil Dynamics and Earthquake Engineering, 2025)

Antibiotic resistance gene transfer characteristic and risk evaluation: The entire process from swine manure to biogas slurry and then to soil - Pengcheng Liang; Hu Wang; Quanxu Chen; Qu Luo; Jianbo Cheng; Guangliang Tian; Tengbing He; Wenhai Zhu; Tianling Fu (Journal of Environmental Chemical Engineering, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Understory plant diversity supports the delivery of ecosystem multifunctionality on the Loess Plateau: A comparative of plantations and natural forests - Guoliang Sha; Huan Yu; Yuxuan Chen; Kang Ren; Pengcheng Xin; Xin Guo; Jing Xiao; Yanchao Fu (Journal of Environmental Management, 2024)

Hydroxyapatite nanoparticle improves ovine oocyte developmental capacity by alleviating oxidative stress in response to vitrification stimuli - Qian Liu; Aiju Liu; Yucheng Liu; Jun Li; Jiachen Bai; Guiping Hai; Jingjing Wang; Weijun Liu; Pengcheng Wan; Xiangwei Fu (Theriogenology, 2024)

Co-application of beneficial microorganisms and nanoparticles to improve wheat growth in infected Fusarium culmorum soil - Marayam Kashisaz; Naeimeh Enayatizamir; Pengcheng Fu; Mohammadreza Eslahi (Applied Soil Ecology, 2024)

High resolution (1-km) surface soil moisture generation from SMAP SSM by considering its difference between freezing and thawing periods in the source region of the Yellow River - Xiaolei Fu; Yuchen Zhang; Luofujie Guo; Haishen Lü; Yongjian Ding; Xianhong Meng; Yu Qin; Yueyang Wang; Bin Xi; Shiqin Xu; Pengcheng Xu; Gengxi Zhang; et al. (Agricultural and Forest Meteorology, 2024)

Enhanced drying of water-containing porous aluminum hydroxide particles via a cyclone based on microchannel oscillation - Aosong Wei; Pengcheng Tao; Li Dai; Jianpeng Hong; Shiyun Li; Wei Zhao; Junjie Liu; Tong Zhang; Pengbo Fu; Hualin Wang (Journal of Environmental Chemical Engineering, 2024)

New tools for effective production and long-term stabilization of microcystinase (MlrA) - A biotechnological perspective towards hepatotoxic microcystins remediation - Jason Dexter; Barbara Klimczak; Antonia Łobodzińska; Aleksandra Tlałka; Pengcheng Fu; Dariusz Dziga (Biocatalysis and Agricultural Biotechnology, 2024)

The risk of viable but non-culturable (VBNC) enterococci and antibiotic resistance transmission during simulated municipal sludge composting - Bingni Zhang; Yulong Fu; Feiyu Wang; Pingri Jin; Pengcheng Xu; Haoming Li; Xiaojie Xu; Chaofeng Shen (Waste Management, 2024)

A dynamic von Mises-based model to evaluate the impact of urbanization and climate change on flood timing in Yangtze and Huaihe River Basins, China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Zhilang Zhang; Xiaosan Shang; Hongyuan Fang; Yangyang Xie; Gengxi Zhang; Saiyan Liu; Xiaolei Fu (Journal of Hydrology, 2024)

Synthesis of nanoparticles using Trichoderma Harzianum, characterization, antifungal activity and impact on Plant Growth promoting Bacteria - Marayam Kashisaz; Naeimeh Enayatizamir; Pengcheng Fu; Mohammadreza Eslahi (World Journal of Microbiology and Biotechnology, 2024)

Effects of Chemical Fixatives on Kinetic Measurements of Biomolecular Interaction on Cell Membrane - Tianbao Dong; Shengyang Wan; Yanhui Wang; Yaru Fu; Pengcheng Wang (The Journal of Membrane Biology, 2024)

Evaluating vegetation vulnerability under compound dry and hot conditions using vine copula across global lands - Gengxi Zhang; Shuyu Zhang; Huimin Wang; Thian Yew Gan; Xiaoling Su; Haijiang Wu; Lijie Shi; Pengcheng Xu; Xiaolei Fu (Journal of Hydrology, 2024)

A time-varying Copula-based approach to quantify the effects of antecedent drought on hot extremes - Pengcheng Xu; Zhilang Zhang; Dong Wang; Vijay P. Singh; Changsheng Zhang; Xiaolei Fu; Leizhi Wang (Journal of Hydrology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

A new coupled depth-integrated model incorporating 3D DDA on debris flow with large boulders - Pengcheng Yu; Xinyan Peng; Guangqi Chen; Haiying Fu; Yingbin Zhang; Zheng Han; Hong Zhang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Structural characterization of polysaccharide fractions in areca (Areca catechu L.) inflorescence and study of its immunological enhancement activity in vitro and in vivo - Di Chen; Jin Li; Qian Gao; Zonghua Kang; Haiming Chen; Pengcheng Fu (Food Research International, 2023)

Isolation and identification of green alga Chlorella vulgaris HNUFU001 for environmental selenium enrichment in heterotrophic growth regime - Zhenyu Zhang; Li Wang; Yinqiang Wu; Chenshuo Li; Pengcheng Fu; Jing Liu (Algal Research, 2023)

Microbial remediation of oil-contaminated shorelines: a review - Xiaoli Dai; Jing Lv; Pengcheng Fu; Shaohui Guo (Environmental Science and Pollution Research, 2023)

Cenozoic basement-involved rifting of the northern South China Sea margin - Yanhui Suo; Sanzhong Li; Guangrong Peng; Xiaodong Du; Jie Zhou; Pengcheng Wang; Guangzeng Wang; Ian Somerville; Yixiao Diao; Zhongqiang Liu; Xinjian Fu; Bo Liu; et al. (Gondwana Research, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

NECL2 regulates blood–testis barrier dynamics in mouse testes - Jun Fu; Xiao Liu; Bin Yin; Pengcheng Shu; Xiaozhong Peng (Cell and Tissue Research, 2023)

Vision meets algae: A novel way for microalgae recognization and health monitor - Shizheng Zhou; Juntao Jiang; Xiaohan Hong; Pengcheng Fu; Hong Yan (Frontiers in Marine Science, 2023)
Marine microalgae are widespread in the ocean and play a crucial role in the ecosystem. Automatic identification and location of marine microalgae in microscopy images would help establish marine ecological environment monitoring and water quality evaluation system. We proposed a new dataset for the detection of marine microalgae and a range of detection methods, the dataset including images of different genus of algae and the same genus in different states. We set the number of unbalanced classes in the data set and added images of mixed water samples in the test set to simulate the actual situation in the field. Then we trained, validated and tested the, TOOD, YOLOv5, YOLOv8 and variants of RCNN algorithms on this dataset. The results showed both one-stage and two-stage object detection models can achieve high mean average precision, which proves the ability of computer vision in multi-object detection of microalgae, and provides basic data and models for real-time detection of microalgal cells.

Detection and attribution of urbanization impact on summer extreme heat based on nonstationary models in the Yangtze River Delta, China - Pengcheng Xu; Yuankun Wang; Xiaolei Fu; Vijay P. Singh; Jianchun Qiu (Urban Climate, 2023)

Regulation mechanism of cyanide production and conversion of Pseudomonas fluorescens commonly used in bio-cyanidation of precious metals from waste printed circuit boards - Mi Lin; Zichun Yao; Pengcheng Wang; Yonggao Fu; Jujun Ruan (Resources, Conservation and Recycling, 2023)

An intelligent model for early kick detection based on cost-sensitive learning - Peng Chi; Li Qingfeng; Fu Jianhong; Yang Yun; Zhang Xiaomin; Su Yu; Xu Zhaoyang; Zhong Chengxu; Wu Pengcheng (Process Safety and Environmental Protection, 2023)

Inulin reduces liver triacylglycerol by increasing lipid droplet lipolysis in fat-loaded mice - Bingbing Chen; Yumeng Shi; Kai Zhang; Yanzhong Chang; Pengcheng Fu; Pingsheng Liu; Shuyan Zhang (Food Research International, 2023)

An Improved Discontinuous Deformation Analysis to Solve Numerical Creep Problem in Shear Direction - Pengcheng Yu; Xinyan Peng; Yingbin Zhang; Dejian Li; Haiying Fu; Yin Cheng (Rock Mechanics and Rock Engineering, 2022)

In silico and in vitro assessment of bioactive peptides from Arthrospira platensis phycobiliproteins for DPP-IV inhibitory activity, ACE inhibitory activity, and antioxidant activity - Jing Liu; Xinpeng Bai; Pengcheng Fu (Journal of Applied Phycology, 2022)

Investigation of permanent displacements of near-fault seismic slopes by a general sliding block model - Yingbin Zhang; Chenlin Xiang; Pengcheng Yu; Lianheng Zhao; John X. Zhao; Haiying Fu (Landslides, 2022)

Enhanced whole-cell biotransformation of 3-chloropropiophenone into 1-phenyl-1-propanone by hydrogel entrapped Chlorella emersonii (211.8b) - Sikandar Khan; Pengcheng Fu; Alessandro Di Fonzo; Irene Marasca; Francesco Secundo (Biotechnology Letters, 2021)

An evaluation into the biosorption and biodegradation of azo dyes by indigenous siderophores-producing bacteria immobilized in chitosan - Theint Theint Win; Tin Myat Swe; Htike Htike Ei; Nwe Nwe Win; Kyi Kyi Swe; Win Nandar; Thet kyaw Ko; Pengcheng Fu (Biodegradation, 2021)

An Enhanced Virtual Crack Closure Technique for Stress Intensity Factor Calculation along Arbitrary Crack Fronts and the Application in Hydraulic Fracturing Simulation - Hui Wu; Randolph R. Settgast; Pengcheng Fu; Joseph P. Morris (Rock Mechanics and Rock Engineering, 2021)

Newly isolated strain of Trichoderma asperellum from disease suppressive soil is a potential bio-control agent to suppress Fusarium soil borne fungal phytopathogens - Theint Theint Win; Bo Bo; Przemyslaw Malec; Sikandar Khan; Pengcheng Fu (Journal of Plant Pathology, 2021)

Combined Use of Bacillus subtilis yb-114,246 and Bacillus licheniformis yb-214,245 Improves Body Growth Performance of Chinese Huainan Partridge Shank Chickens by Enhancing Intestinal Digestive Profiles - Jiajun Yang; Kehe Huang; Jing Wang; Dong Wu; Zongliang Liu; Pengcheng Yu; Zhanyong Wei; Fu Chen (Probiotics and Antimicrobial Proteins, 2021)

Transgenic eukaryotic microalgae as green factories: providing new ideas for the production of biologically active substances - Qianwen Shi; Cheng Chen; Wei Zhang; Ping Wu; Meng Sun; Hui Wu; Haizhen Wu; Pengcheng Fu; Jianhua Fan (Journal of Applied Phycology, 2021)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Long non-coding RNA RP11-6O2.4 indicates poor prognosis and suppresses cell cycle progression through the p38-MAPK signaling pathway in gastric cancer - Yang Feng; Zhiming Fu; Yajun Luo; Wang Tan; Zilin Liu; Pengcheng Ye; Fei Lu; Wanping Xiang; Linghan Tang; Lin Yao; Mengyun Song; Qingmei Huang; et al. (Molecular & Cellular Toxicology, 2019)

Verification of soman-related nerve agents via detection of phosphonylated adducts from rabbit albumin in vitro and in vivo - Feiyan Fu; Runli Gao; Ruihua Zhang; Pengcheng Zhao; Xiaogang Lu; Liqin Li; Hongmei Wang; Chengxin Pei (Archives of Toxicology, 2019)

Evaluating a Simple Fracturing Criterion for a Hydraulic Fracture Crossing Stress and Stiffness Contrasts - Jixiang Huang; Pengcheng Fu; Randolph R. Settgast; Joseph P. Morris; Frederick J. Ryerson (Rock Mechanics and Rock Engineering, 2019)

Antiviral activity of recombinant porcine surfactant protein A against porcine reproductive and respiratory syndrome virus in vitro - Lan Li; Qisheng Zheng; Yuanpeng Zhang; Pengcheng Li; Yanfeng Fu; Jibo Hou; Xilong Xiao (Archives of Virology, 2016)

Thermal Drawdown-Induced Flow Channeling in Fractured Geothermal Reservoirs - Pengcheng Fu; Yue Hao; Stuart D. C. Walsh; Charles R. Carrigan (Rock Mechanics and Rock Engineering, 2016)

NDH-1L interacts with ferredoxin via the subunit NdhS in Thermosynechococcus elongatus - Zhihui He; Fangfang Zheng; Yaozong Wu; Qinghua Li; Jing Lv; Pengcheng Fu; Hualing Mi (Photosynthesis Research, 2015)